On rheology of cross-linked polymers: 1. Slippage of polymer chains and its macroscopic modeling. (March 2016) - Berdichevsky, Victor L.; Herman, John N.
Abstract: A model is proposed to describe the rheologic behavior of cross-linked polymers. It is based on hypotheses of the micromechanical origin of the time-dependent behavior. Starting from the dynamics of one polymer chain, a complete thermodynamic description and a closed system of equations governing the deformation of polymers and polymer foams is constructed. The first paper of the two-paper series is concerned with the theory, while the second describes the experimental results on creep and stress relaxation in polymethacrylimide foams and compares the results with theoretical predictions.